Kontestasi Narasi Moderasi Beragama di Instagram - Hasan Albana (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2022)
People who study religion are no longer limited to religious leaders who have direct scientific legitimacy. However, it can be done independently through the internet or social media. Religious narratives that develop on the internet or social media can caontradict one another, such as narratives about religious moderation. This study aims to map the contestation of religious moderation narratives that develop on social media and to see religious ideologies that reject the concept of religious moderation on social media. This study uses a qualitative approach and descriptive method, data collection techniques using document studies from posts on Instagram. The findings of this study show that the narratives that support about religious moderation include the definition of religious moderation, the characteristics of moderate people, the urgency of religious moderation, examples of moderate behavior in religion, religious moderation in Islam, religious moderation in Buddhism, principles of religious moderation, local wisdom and religious moderation, and steps taken by the Ministry of Religion to strengthen religious moderation. Meanwhile, the narrative that rejects religious moderation is in the form of explaining that religious moderation as a half-hearted religion, contrary to Islam, not including kaffah Islam, is a western product, hinders the rise of Muslims, hinders the establishment of the caliphate.